Hyaline Globules in Epithelial Neoplasm of Kidney - Gao, Chen; D’Angelis, Chris; Qiu, Jingxin; Xu, Bo (North American Journal of Medicine and Science, 2013)
Hyaline globules (HGs) are eosinophilic inclusion bodies found in many benign and malignant tumors as well as in non-neoplastic tissues. It has been reported that renal epithelial tumor cells may contain variable amounts of HGs that can be stained red by Masson’s trichrome. Intracytoplasmic HGs are occasionally found in renal cell carcinoma (mainly clear cell and papillary RCC) and are thought to be associated with high Fuhrman nuclear grade and metastasis. In contrast, extracellular HGs most often occur in benign epithelial tumors such as oncocytoma. The biological significance and nature of HGs are not clear. It has been speculated that HGs may represent a stage of tumor cell apoptosis. In this review, we report a case of clear cell renal cell carcinoma with extensive intracellular HGs. The histological, cytochemical, immunohistochemical, and ultrastructural characteristics of HGs are reviewed and their clinical significance is discussed. In addition, other types of inclusions occurring in the tumors of the kidney are also briefly summarized.